Defective transmission of passive immunity in dairy farm calves. - Aroyo-Arroyo, Juan José (2014)
The objective of this study was to determine the prevalence of failure of passive transfer of immunity of dairy heifer calves for the third consecutive year in the Northern Plains of Costa Rica. The data correspond to total serum protein (TSP) measurements obtained during the period of August and November of 2012 in 23 dairy farms. 657 female calves were sampled. The breeds of the cows were classified into Holstein, Jersey, Holstein × Jersey crosses and others. For the purpose of this study, failure of passive immunity was considered when TSP concentration was less than 5.5 g/dl. TSP concentration ranged from 2.4 to 10.0, with an overall mean of 5.7 g/dl. Of all the calves evaluated, 44.9% presented failure of passive transfer. Calves born to Jersey and Holstein x Jersey crosses had significantly higher TSP concentrations than calves born to Holstein and other breeds. When considering calving of the dam, there were no significant differences on TSP concentration, however offsprings born to third lactation cows showed the lowest percentage of animals with inadequate transfer of immunity. The findings of this study suggest that colostrum management practices should be placed in order to minimize the risk of failure of passive transfer of immunity in dairy herds in the Northern Plains of Costa Rica.